1996
DOI: 10.1002/hep.510240551
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in bilirubin and jaundice: Report of the Third International Bilirubin Workshop, April 6-8, 1995, Trieste, Italy

Abstract: only partial and temporary relief of hyperbilirubinemia; tocytic transporters of UCB and related organic anions extracorporeal liver assist devices have had some sucwere described. Special emphasis was given to the adencess in initial human studies; and inhibition of heme osine triphosphate (ATP)-dependent canalicular multioxygenase (HO) with metalloporphyrins, especially tin specific organic anion transporter that is defective in mesoporphyrin, which markedly decreases bilirubin production for prolonged perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 204 publications
2
14
0
1
Order By: Relevance
“…Indeed, over a decade ago, the use of metalloporphyrins as therapeutic agents against hyperbilirubinemia was recommended (Drummond and Kappas 1981;Galbraith et al 1992;Martinez et al 2001). Despite this potential clinical application of the metalloporphyrins, the mainstay of managing hyperbilirubinemia has been phototherapy and exchange blood transfusion (Tiribelli and Ostrow 1996;Dennery 2005). This may be due to the lack of selectivity associated with metalloporphyrins as therapeutic drug candidates ( Table 2).…”
Section: Adverse Effects Of Bilirubinmentioning
confidence: 96%
“…Indeed, over a decade ago, the use of metalloporphyrins as therapeutic agents against hyperbilirubinemia was recommended (Drummond and Kappas 1981;Galbraith et al 1992;Martinez et al 2001). Despite this potential clinical application of the metalloporphyrins, the mainstay of managing hyperbilirubinemia has been phototherapy and exchange blood transfusion (Tiribelli and Ostrow 1996;Dennery 2005). This may be due to the lack of selectivity associated with metalloporphyrins as therapeutic drug candidates ( Table 2).…”
Section: Adverse Effects Of Bilirubinmentioning
confidence: 96%
“…Subsequent biochemical studies progressively delineated which UGT isoforms were present and active [128,132] culminating in the first isoform-specific studies from Strassburg et al who showed that although fetal levels of mRNA and protein for UGT isoforms did not differ from adults, activities were lower for up to 2 years of age [36]. Subsequently, the pediatric ontogeny of several hepatic UGT1A and UGT2B isoforms has been described [36][37][38][39][121][122][123][124][125][126] although the development of UGT enzymes in other neonatal tissues is not well understood. The liver studies have demonstrated that although mRNA and protein are present, glucuronidation does not mature for several months after birth, with maturation of individual UGT enzymes each under separate developmental controls [37][38][39]121,126].…”
Section: Ontogenetic Regulation Of Ugtmentioning
confidence: 98%
“…While this is not always true, the UGT enzymes are an example of a critical drug elimination pathway that does not mature until after birth [36][37][38][39][121][122][123][124][125][126]. Although UGTs can be detected as early as the blastocyst stage in mammalian development (indicating a possible role in embryology) [127] in fetal red blood cells and in the fetal liver [128][129][130], glucuronidation activity has not been detected until 30 --40 weeks of gestation [122,123].…”
Section: Ontogenetic Regulation Of Ugtmentioning
confidence: 99%
“…Together, these data indicate that drug-induced bilirubin elevation might initially result from a decrease in hepatocellular ATP. Bilirubin processing includes several steps that are likely ATP-dependent, e.g., bilirubin conjugation and export from the hepatocyte (Tiribelli and Ostrow, 1996; Paulusma et al, 1997; Borst et al, 2007). Using the DILIsym™ model, APAP was simulated in the presence or absence of an ATP contribution to bilirubin generation.…”
Section: Liver Modeling Case Studiesmentioning
confidence: 99%